Analisis Kualitas Produk Dan Kepercayaan Merek Terhadap Loyalitas Merek - Viscal Muhamad Khalis; Kokom Komariah; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this research is to measure how much influence product quality and brand trust have on brand loyalty. The method used in this study is a quantitative method with descriptive and associative methods. The population in this study were customers of PT. INSPIRA SNACK BARING CHIPS Sukabumi City and the sample used is 150 respondents. The data analysis technique used is multiple linear regression which in this method uses the partial influence method and the simultaneous effect and the sample technique used is saturated sampling. The results obtained indicate a positive and significant influence. The f test results show that the independent variables, namely product quality and brand trust, have a positive and significant influence on the dependent variable, namely brand loyalty. with a value of Fcount 104.097 > 3.06 Ftable. While the coefficient of determination (Adjusted R2) is 0.586, which means that the effect of product quality and brand trust on brand loyalty is 59% and the remaining 41% is influenced by other factors not examined. The results of the t test show that the product quality variable has a Tcount value of 6.841 > 1.976 T table and a significant value of 0.000 < 0.05, which means that there is a positive and significant effect between product quality on brand loyalty. Then the brand trust variable has a Tcount of 4.436 > 1.976 and a significant value of 0.000 <0.05, which means that there is a positive and significant influence between brand trust and brand loyalty. Keywords: Product Quality, Brand Trust, Brand Loyalty